B7 family protein glycosylation: Promising novel targets in tumor treatment - Xiao, Linlin; Guan, Xiaoyan; Xiang, Mingli; Wang, Qian; Long, Qian; Yue, Chaoyi; Chen, Lulu; Liu, Jianguo; Liao, Chengcheng (Frontiers in Immunology, 2022)
Cancer immunotherapy, including the inhibition of immune checkpoints, improves the tumor immune microenvironment and is an effective tool for cancer therapy. More effective and alternative inhibitory targets are critical for successful immune checkpoint blockade therapy. The interaction of the immunomodulatory ligand B7 family with corresponding receptors induces or inhibits T cell responses by sending co-stimulatory and co-inhibitory signals respectively. Blocking the glycosylation of the B7 family members PD-L1, PD-L2, B7-H3, and B7-H4 inhibited the self-stability and receptor binding of these immune checkpoint proteins, leading to immunosuppression and rapid tumor progression. Therefore, regulation of glycosylation may be the “golden key” to relieve tumor immunosuppression. The exploration of a more precise glycosylation regulation mechanism and glycan structure of B7 family proteins is conducive to the discovery and clinical application of antibodies and small molecule inhibitors.